The effect of gracilaria sp on the water quality of semi-intensive shrimp pond effluent. - Lamis, Rovi May (1994.)
The effect of Gracilaria sp at various sampling periods on the physical and chemical properties of semi-intensive shrimp pond effluent was studied in a completely randomized design with three replicates. The treatments consisted of 34 liters shrimp pond effluent and different amounts of Gracilaria sp. (200 grams, 400 grams and 600 grams). Effluent sample without Gracilaria sp served as control., The experiment was conducted for two weeks at the University of the Philippines Brackishwater Aquaculture Center, Leganes. Sampling periods were: start of the experiment, after one week and after two weeks of experiment. In general, ammonia-nitrogen content, phosporus content, pH and dissolved oxygen (DO) are water quality factors considered to indicate degree of pollution in water. In aquaria without Gracilaria sp, a higher level of ammonia-nitrogen and phosphorus was observe, while in aquaria with various amounts of Gracilaria sp., significance (@=0.05) decrease in ammonia-nitrogen and phosphorus was observed at various sampling periods. Water were relatively low at the start of the experiment. However, in aquaria with Gracilaria sp a significant (@=0.05) increase was observed after one week due to photosynthetic activity. Bacterial decomposition probably decreased water pH during the second week to a level that would not pose a threat to the environment. Dissolved oxygen level decreased significantly (@=0.05) in aquaria without Gracilaria sp and in aquaria containing 200 grams at various sampling periods, indicating a slight pollution.
Thesis (Undergraduate, Bachelor of Science in Biology) College of Arts and Sciences, University of the Philippines in the Visayas, Iloilo City.
Keywords: Shrimp Ponds -- Water quality